Topics in the Research of E-book Usage and the Applicable Findings of it for Product Development - Légrádi , Miklós (International Journal of Engineering and Management Sciences, 2020)
This article aims to review the recent academic researches on print and e-book usage experience and preferences. Their findings will be compared to the results of a primary research previously conducted by the author. Using these data the article presents the Five Product Level of e-books and e-readers. Reviewing the Hungarian and International e-book / print sales figures and publishing trends, the article shows ways for further research for a better e-book product understanding and highlights a few promising ways for future product development in e-books and e-readers.